Optimal monetary policy in a model of the credit channel - Fiorella De Fiore; Oreste Tristani (European Central Bank (ECB), 2009)
We consider a simple extension of the basic new-Keynesian setup in which we relax the assumption of frictionless financial markets. In our economy, asymmetric information and default risk lead banks to optimally charge a lending rate above the risk-free rate. Our contribution is threefold. First, we derive analytically the loglinearised equations which characterise aggregate dynamics in our model and show that they nest those of the new- Keynesian model. A key difference is that marginal costs increase not only with the output gap, but also with the credit spread and the nominal interest rate. Second, we find that financial market imperfections imply that exogenous disturbances, including technology shocks, generate a trade-off between output and inflation stabilisation. Third, we show that, in our model, an aggressive easing of policy is optimal in response to adverse financial market shocks.
Keywords: E52; E44; 330; Asymmetric information; financial markets; optimal monetary policy; Geldpolitik; Finanzmarkt; Schock; Asymmetrische Information; Neoklassische Synthese